Peningkatan Omzet UMKM Makanan Ringan Pasca Sertifikasi Halal di Sumatera Barat - Nenengsih, Nenengsih; Muslim, Mulyadi (AL-Muqayyad, 2024)
The SMEs sector in snack food plays a significant role in economic advancement. Efforts to promote SMEs in the snack food industry include obtaining halal certification. Previous research has mainly focused on the influence of halal certification on the revenue of SMEs in the food sector. However, there hasn't been a model established for increasing the sales revenue of SMEs in the snack food industry. The objective of this research is to determine the changes in sales turnover of snack food SMEs in West Sumatra after obtaining halal certification and the factors influencing these changes.The research approach used was quantitative, and data were collected through questionnaires and structured interviews with 27 owners of SMEs in the snack food industry. The analysis methods employed were descriptive analysis, t-tests, and SEM-PLS analysis. The research results show that halal certification has a significant relationship with the increase in sales turnover of snack food SMEs in West Sumatra. Factors such as the number of employees, working hours, the age of the SMEs, business capital, and the halal certification process also have a significant impact on the increase in sales turnover after halal certification.